Do Remittances Reduce Aid Dependency? - Le Goff, Maelan (IMF Working Papers; Working Paper, 2011)
Aid has been for decades an important source of financing for developing countries, but more recently remittance flows have increased rapidly and are beginning to dwarf aid flows. This paper investigates how remittances affect aid flows, and how this relationship varies depending on the channel of transmission from remittances to aid. Buoyant remittances could reduce aid needs when human capital improves and private investment takes off. Absent these, aid flows could still drop as remittances may dampen donors' incentive to scale up aid. Concurrently, remittances could be positively associated with aid if migrants can influence aid policy in donor countries. Using an instrumental variable approach with panel data for a sample of developing countries from 1975-2005, the baseline results show that remittances actually increase aid dependency. However, a refined model controlling for the channels of transmission from remittances to aid reveals that remittances lead to lower aid dependency when they are invested in human and physical capital rather than consumed.